Complexity analysis of a matchmaker based on hidden Markov model for decentralised grid scheduling. (1st January 2014) - Bolívar, H.; Martínez, M.; González, R.; Sanjuán, O.
The design of scheduling algorithms for a heterogeneous computing system interconnected with an arbitrary communication network is one of the main concerns in distributed systems research, due to the heterogeneous nature of resource, computing capacity, memory, devices, internet and institutional policies. Different models have been proposed for the scheduler, which contemplate point-to-point communication to allow the direct exchange of information and provide more flexibility to the planning within the open systems. This balances the load of the system, improves interoperability between the components, the management of resources, performance, reliability and a high degree of scalability. However, related works assumed the lack of control of the resource by scheduler. We propose the analysis of theoretical and experimental complexity of an algorithm based on hidden Markov models because it facilitates the prediction of availability of the grid resources and can evolve over time.